2008
DOI: 10.3402/ijch.v67i4.18343
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial hyperresponsiveness in a population of north Finland with no previous diagnosis of asthma or chronic bronchitis assessed with histamine and methacholine tests

Abstract: Objectives. To assess the prevalence of bronchial hyperresponsiveness (BHR) in a population of north Finland among subjects with no previous diagnosis of asthma or chronic bronchitis by using histamine and methacholine challenges. The agreement between the methods was also evaluated. Study design. An epidemiological study assessing the prevalence of BHR measured with direct dosimetric challenge methods. Methods. Seventy-nine randomly selected subjects ( 1-73 years) were studied; 67% had respiratory or allergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…In this study, female gender and BHR showed no association in contrast with some other's findings (8, 41, 42). The explanation may, at least in part, depend on differences in cohorts’ lung-function values or the use of that data.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In this study, female gender and BHR showed no association in contrast with some other's findings (8, 41, 42). The explanation may, at least in part, depend on differences in cohorts’ lung-function values or the use of that data.…”
Section: Discussioncontrasting
confidence: 92%
“…In Finland, the prevalence of physician-diagnosed asthma in adults has increased to 7% (6, 7), but epidemiologic data on BHR and its associations are available only from a selected study cohort from near the Arctic Circle (8). …”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of BHR in the general Finnish population with no previous diagnosis of asthma or chronic bronchitis and with normal lung volumes is 17% [37]. In our study population, BHR occurred markedly more frequently in 41%, which is in accordance with the results of other studies [9,18,20,36].…”
Section: Thoracic Surgerysupporting
confidence: 82%
“…International guidelines of Bronchial Provocation Test still consider histamine and methacholine as alternative methods to express BHR. Methacholine and histamine are nearly equipotent direct bronchoconstrictors (30,31), and thereby histamine and methacholine positivity are likely to express the same pathophysiology in the study groups. In contrast, EVH represents indirect stimuli for the measurement of BHR, corresponding more closely exercise test (32) and is widely recommended for the diagnosis of EIB in athletes (13).…”
Section: Discussionmentioning
confidence: 94%